PENGARUH PENAMBAHAN SERBUK BATA MERAH TERHADAP STABILITAS TANAH LEMPUNG SEBAGAI TANAH DASAR JALAN - Moch. Sholeh; Dandung Novianto (Media Teknik Sipil, 2012)
Moch. Sholeh1 & Dandung Novianto21 & 2Fakultas Teknik Jurusan Teknik Sipil Politeknik Negeri MalangABSTRACTClay consists of grains - grains are very small (<0002 mm) and shows the nature - the natureof plasticity and cohesion. Cohesion indicates the fact that part - the part that is attached to eachother, while the plasticity is a trait that allows the form of the material was changed - edit withoutchanging the content or without returning to its original form, and without any cracks or brokens.And clay with high plasticity index has strong support low when used as a basic foundation of thehighway, so the need for soil improvement.From the above problems then this study aims to engineer clay with red brick powder in fourcomparisons. The first native land. Both the original soil mixed with red brick powder 5%. The thirdnative soil mixed with red brick powder 7.5%. The four original soil mixed with red brick powder10%. Each of these sought specific gravity, liquid limit, plastic limit and plasticity index on theoriginal soil, mixing 5%, 7.5% and 10%. From the analysis of data obtained the following conclusion:the original soil, the value amounting to 60.9 Liquid limit, plastic limit values of 42.8 and plasticityindex value of 18.1. The most optimal additional percentage is 7.5%. And Plasticity Index value at7.5% is 20,31.Key words : Red brick powder, Soil Stability, Subgrade and the Road